Economic Growth Inclusivity in Sumatra Province - Irmanelly Irmanelly; Amri Amir; Zamzami Zamzami; Syaparuddin Syaparuddin (Budapest International Research and Critics University, 2022)
The purpose of this research using a static panel regression model is to analyze the effect of inclusive growth through the World Economic Forum (WEF) indicator on income inequality and poverty in Sumatra Province, where partially inclusive economic growth has a positive and significant effect on income inequality during the 2007-2020 period at the regressor error rate of 5% or 0.0637 with a determination value of R2 of 0.0247 and a constant value of 5.9561 or with t-count> t-table value of (1.8695> 1.6450). Meanwhile, for analysis purposes, the effect of inclusive growth on poverty partially has a positive and significant effect on the regression error rate of 5% or 0.0008 with an R2 value of determination of 7.85% at a constant value position of 0.0068 with proof t-count value and t table (3.3401 > 1.6450). The findings of this study indicate that government policies need to maintain law enforcement and be able to increase state income to ensure social protection for the community in a fair and equitable manner as well as guarantee the right of every citizen to obtain a decent income and reduce the level of income inequality happening in society.